Środki alternatywne wobec kary pozbawienia wolności - Szczygieł, Grażyna B. (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In the catalog of penalties imprisonment emerged as penalty signifying progress and improvement of customs. Numerous defects identified prompted the search for alternative measures. The result of this search is the development, on the international forum — both in the universal and regional planes, of alternatives to imprisonment and the rules for their application. Given that in our country the population of prisoners serving a term of imprisonment as well as awaiting it is steadily increasing, it seems appropriate to search for the causes of this condition, especially that such a situation is not justified by the increase in the number of crimes committed. A glimpse at the existing regulations and the practice emerging from them warrants the works on amendments to the codification of the criminal law.
Keywords: kara pozbawienia wolności; alternatywy dla pozbawienia wolności; probacja (prawo)